A variant epidermal growth factor receptor exhibits altered type alpha transforming growth factor binding and transmembrane signaling. - Moriai, T (1994)
Epidermal growth factor (EGF) and type alpha transforming growth factor (TGF-alpha) bind to a specific region in subdomain III of the extracellular portion of the EGF receptor (EGFR). Binding leads to receptor dimerization, auto-and transphosphorylation on intracellular tyrosine residues, and activation of signal transduction pathways. We compared the binding and biological actions of EGF and TGF-alpha in Chinese hamster ovary (CHO) cells expressing either wild-type human EGFR (HER497R) or a variant EGFR that has an arginine-to-lysine substitution in the extracellular domain at codon 497 (HER497K) within subdomain IV of EGFR. Both receptors exhibited two orders of binding sites with radioiodinated EGF (125I-EGF). Similar results were obtained with 125I-TGF-alpha in cells expressing HER497R. In contrast, only one order of low-affinity binding sites was seen with 125I-TGF-alpha in the case of HER497K. Although EGF and TGF-alpha enhanced tyrosine phosphorylation of both receptors, CHO cells expressing HER497K exhibited an attenuated growth response to EGF and TGF-alpha and a reduced induction of the protooncogenes FOS, JUN, and MYC. Moreover, high concentrations of TGF-alpha (5 nM) inhibited growth in these cells but not in cells expressing HER497R. These findings indicate that a region in subdomain IV of EGFR regulates signal transduction across the cell membrane and selectively modulates that binding characteristics of TGF-alpha.